Peran Wali Songo (Sunan Bonang) dengan Media Da’wah dalam Sejarah Penyebaran Islam di Tuban Jawa Timur - Warsini Warsini (ASANKA : Journal of Social Science and Education, 2022)
The purpose of this article is to describe: 1) The role of Wali Songo (Sunan Bonang) in the spread of Islam in Tuban, East Java, 2) The media used by Wali Songo (Sunan Bonang) in the spread of Islam in Tuban, East Java, 3) History of the process of entering Islam in Indonesia. Tuban, East Java. The research process is carried out by taking literature studies from literature, books, and from the internet. Then the relevant studies and studies are carried out. To discuss the results of the study, a description was carried out by linking from literature, books and from the internet. Then conclude the research results that have been pursued in accordance with the objectives of this research, namely: The role of Wali Songo (Sunan Bonang) in the spread of Islam in Tuban, East Java is to acculturate religion and culture so that the Islamization process in Tuban runs peacefully. Da'wah media used in the spread of Islam in Tuban, East Java include culture, Sufism, art, higher education, wayang, and Suluk. The history of the entry of Islam in Tuban, East Java because the Islamic kingdom in Tuban embraced Islam and had good relations with the Majapahit kingdom which led to the easy spread of Islam in the northern coastal lands of Java